Psychometric Properties of the Big Five Questionnaire for Children in a Sample of Kuwaiti University Undergraduates - Bader M. Al Ansari; Talal B. Al Ali (Sultan Qaboos University, 2018)
This study aimed to examine: (1) the internal consistency and the test-retest reliability of the Big Five Questionnaire for Children (BFQ-C) developed by Barbaranelli et al., (2003); (2) its five factor structure and (3) the criterion validity of the BFQ-C. The sample consisted of 745 Kuwaiti university undergraduate students (333 males, 412 females). Their age average was (M= 19.58  (SD = 1.12)). The results showed that Cronbach alpha's indicated high internal consistency. Principle components analysis showed that most of the items loaded convincingly on to their factors. The criterion validity of the BFQ-C was acceptable to high. It was concluded that the Arabic version of the BFQ-C could be used successfully with Kuwaiti university undergraduate students.